Nanowave your steaks from cow genes. - De Botton, Alain (New Statesman & Society, 1995)
The writer discusses the science program, Horizon's Nanotopia, presented on British television in November 1995. The program examined nanotechnology, which is the latest scientific breakthrough concerned with constructing machines so minute that they can rearrange matter atom by atom and thereby create limitless quantities of the most precious materials. Advanced science is too complicated to be understood by common sense, and science program makers should therefore accept that one TV program is not enough to explain the workings of nanotechnology. Sad though it may be, the viewer without a physics PhD should just be allowed to take nanotechnologists' word for it.